The Effect of Anticipatory Pleasure Skills Training Program on Anhedonia Among Patients with Major Depressive Disorder - Teriyapiom, Jirawat; Thepprasong, Sakaorat (Journal of Nursing and Public Health Research, 2021)
The objective of this quasi-experimental, namely two-group pretest-posttest design, was to examine the effect of anticipatory pleasure skills training program on anhedonia among patients with major depressive disorder. Participants were 50 patients with major depressive disorder, aged 18-59 years old, both males and females who were being treated in the inpatient department of Suanprung Psychiatric Hospital. All participants were randomly assigned to the experimental group or the control group, 25 inpatients in each group. The experimental group received the anticipatory pleasure skills training program, whereas the control group received the regular nursing care routine. This study was conducted between June 2020 and Ocotober 2020. The research instruments included the anticipatory pleasure skills training program, the anhedonia scale, and the temporal experience pleasure scale. Data were analyzed using descriptive statistics (percentages, mean and standard deviation). The Wilcoxon sign rank and the Mann-Whitney U tests were used to compare the pretest and posttest average scores of anhedonia between the experimental group and the control group. The results revealed that after receiving the anticipatory pleasure skills training program, the mean score of anhedonia of patients with major depressive disorder in the experimental group was significantly lower than before enrolling the program (p-value <0.001). In addition, the mean score of anhedonia among patients with major depressive disorder in the experimental group was also significantly lower than patients in the control group that receiving the regular nursing care routine (p-value <0.001). This research indicated that the anticipatory pleasure skills training program can reduce anhedonia levels of patients with major depressive disorder. This program could be an additional treatment option psychosocial rehabilitation for patients with major. Nurses and other health care providers can apply or develop this program to other patients with bipolar disorder and postpartum depression in order to reduce anhedonia levels.